Accelerated forgetting of real-life events in Transient Epileptic Amnesia. - Muhlert, N; Milton, F; Butler, C; Kapur, N; Zeman, A (2010)
Transient Epileptic Amnesia (TEA) is a form of temporal lobe epilepsy associated with ictal and interictal memory disturbance. Some patients with TEA exhibit Accelerated Long-term Forgetting (ALF), in which memory for verbal and non-verbal material is retained normally over short delays but fades at an unusually rapid rate over days to weeks. This study addresses three questions about ALF in TEA: (i) whether real-life events undergo ALF in a similar fashion to laboratory-based stimuli; (ii) whether ALF can be detected within 24h; (iii) whether procedural memories are susceptible to ALF. Eleven patients with TEA and eleven matched healthy controls wore a novel, automatic camera, SenseCam, while visiting a local attraction. Memory for images of events was assessed on the same day and after delays of one day, one week, and three weeks. Forgetting of real-life events was compared with forgetting of a word list and with performance on a procedural memory task. On the day of their excursion, patients and controls recalled similar numbers of primary events, associated secondary details (contiguous events, thoughts and sensory information) and items from the word list. In contrast, patients showed ALF for primary events over three weeks, with ALF for contiguous events, thoughts and words over the first day. Retention on the procedural memory task was normal over three weeks. The results indicate that accelerated forgetting in TEA: (i) affects memory for real-life events as well as laboratory stimuli; (ii) is maximal over the first day; and (iii) is specific to declarative memories.